Evaluasi Rambu Lalu Lintas Dan Marka Jalan Ruas Veteran Utara Dan Veteran Selatan - Setyawan P., Arkham; Mallawangeng, Tamrin; Yunianti, Nurhadijah (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
The empirical phenomenon of transportation problems, mainly on the Veteran Utara – Veteran Selatan section, is traffic and lack of driver discipline, causing traffic circulation disturbances, especially on the Veteran Utara – Veteran Selatan road section, which is irregular on a regular basis for road users to the presence of signs and roads. The aim of the research is to determine the placement and need for signs and road markings in North Veteran and South Veteran and to determine the influence of the placement of road signs and markings on North Veteran and South Veteran roads.As for the results of the study, the most severe existing locations are roads that have reverse signposts but do not have facilities for turning back so as to increase road users and increase the potential for accidents, while for the placement of markings there are still many locations that require re-marking because they are starting to fade markings along STA 0+000 – STA 0+3000 are like longitudinal dotted lines and markings crossing the stop line (zebra cross), with the fading of these markings will reduce the level of discipline of road users and increase the potential for traffic accidents